The Development of an Instruction Model for Hearing Impaired Undergraduate Students in Higher Education Institutions - Nayong, Supin (Scholar: Human Sciences, 2015)
The purpose of this study is twofold. The first is to ascertain the current state-of-the art of university instruction for hearing-impaired students. The second is to develop a model to be used as a guide for institution of higher learning in implementing instructional procedures for the hearing-impaired students. A documentary research methodology, employing content analysis was used. Documents scrutinized included self-audit reports, course syllabi, and documents relating to curriculum and instruction and other related administrative materials. The results of the first phase of this analysis were subsequently integrated with conclusions of the second phase of the same endeavors on theories, principles and practices on higher educational instruction for hearing-impaired students, both in Thailand and aboard. Altogether 2,954 titles of were studied. The purposed model derived from the result of the documentary analysis consisted of two parts. First part delineated the scope of perception and understanding of students according to instructional objectives proposed by Marzano and Kendall,(2008), as follows: (1) retrieval with subsets of recognizing, recalling and executing; (2) comprehension with subsets of integrating, symbolizing; (3)analysis with subsets of matching, classifying, analyzing errors, generalizing, specifying; (4) knowledge utilization with subsets of decision making, problem solving, experimenting, investigating; (5) met cognition with subsets of specifying goals, process monitoring, monitoring clarity, monitoring accuracy; (6) self-system thinking with subsets of examining importance, examining efficacy, examining emotional response and motivation. The second part is the proposed instructional model comprising of (1) principle focusing on meeting special needs of hearing-impaired students and their idiosyncrasies; (2) objectives regarding modalities, competency development, cooperation inducement, adaptability towards harmony in one‘s community and academic achievements; (3) instructional deliveries, stressing expected roles of faculty members teaming with Thai Sign Language interpreters and lesion plans designed to make concrete experience become comprehensible in abstract terms; (4) instructional activities emphasizing kinesthetic and visual group dynamics in collaborative styles; (5) Two tiers of evaluation was recommended. Authentic assessment is suggested for student academic achievements whereas student instructional behaviors are to be assessed by the instructional domains (Marzano and Kendall, 2008). Highlights of findings are indispensable instructional systems of learner‘s preparation prior to the actual instructional deliveries, including the creation of optimal environment. Important actions for highest possible student achievements are engaging, framing, acquiring, elaborating and connecting. Positive reinforcements are to be important tools in sustaining cognitive abilities, especially, in thinking, feeling and willing. Significant findings indicate the discovery of effective substitution of deprived audio modality by visual and kinesthetic counterparts.